Comparative Study of Machine Learning Approach on Malay Translated Hadith Text Classification based on Sanad - Mohammad Najib S.R.; Abd Rahman N.; Kamal Ismail N.; Alias N.; Alias M.N.; Zulhilmi Mohamed Nor (EDP Sciences, 2024)
Indexed by SCOPUS